2014
DOI: 10.1093/abbs/gmu088
|View full text |Cite
|
Sign up to set email alerts
|

miR-183 potentially inhibits NF-κB1 expression by directly targeting its 3′-untranslated region

Abstract: Nuclear factor-kB (NF-kB) is an important transcription factor. While the NF-kB signaling pathway is modulated by many microRNAs (miRNAs), very few have been reported to target NF-kB1 gene directly. In this study, we used multiple miRNA target prediction programs to predict miRNAs with putative NF-kB1 3 0 -untranslated region (UTR) binding sites. miR-183 was strongly implicated and experimentally validated by reporter assays. The results showed a reduced expression of the NF-kB1 3 0 UTR containing luciferase v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…A recent report demonstrated that miR‐183 inhibits NF‐κB by directly targeting its 3′‐untranslated region (Sha et al . ). In addition, miR‐183 is known to negatively regulate cell migration in cancer cells (Lowery et al .…”
Section: Introductionmentioning
confidence: 97%
“…A recent report demonstrated that miR‐183 inhibits NF‐κB by directly targeting its 3′‐untranslated region (Sha et al . ). In addition, miR‐183 is known to negatively regulate cell migration in cancer cells (Lowery et al .…”
Section: Introductionmentioning
confidence: 97%
“…Extensive studies have demonstrated that miRNA can effectively alleviate myocardial injury induced by myocardial I/R through direct or indirect anti‐inflammatory mechanisms . NF‐κb has an important role in inflammatory mechanisms, meanwhile, some previous studies reported NF‐κb was an target gene of miRNA‐183 . We inferred that miRNA‐183 overexpression may have effects to improve myocardial damager through NF‐kb pathway.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] NF-κb has an important role in inflammatory mechanisms, meanwhile, some previous studies reported NF-κb was an target gene of miRNA-183. 9,10 We inferred that miRNA-183 overexpression may have effects to improve myocardial damager through NF-kb pathway.…”
Section: In Vivo Study Of the Relative Proteins' Expressions By Immun...mentioning
confidence: 95%
See 1 more Smart Citation
“…miRNA and NF-κB studies revealed the NF-κB-miRNA network, which provides a better understanding of the regulation and cooperation of inflammation and cancer in various cancer types [35][36][37] . In addition to inducing expression, miRNAs repress NF-κB by direct targeting 38 .…”
mentioning
confidence: 99%